The effects of tualang honey on sperm profile and follicular-stimulating hormone in high cholesterol diet-induced animal model - Hasan, Sakiinah; Abdul Rahim, Roslina; Alias, Mohd Afzal; Muhammad, Siti Aesah @ Naznin; Abdullah, Nor Zamzila; Abdul Razak, Redzuan Nul Hakim; Ismail, Faridah (IIUM Press, 2023)
Hypercholesterolaemia is a factor that disturbs cholesterol homeostasis in the body, which may adversely affect the post-testicular maturations and normal male reproductive functions which leads to infertility (Whitfield et al., 2015). However, currently, there is limited therapy available. Tualang honey (TH) is a type of Malaysian polyfloral wild honey generated by the rock bee (Apis dorsata) that has been proven to exert both anti-inflammatory and antioxidative effects as it contains a high level of flavonoids and phenolic acids (Sarfaz & Nor Hayati, 2013). Nevertheless, there is still a lack of studies on the effects of Tualang honey on the sperm profile and follicular-stimulating hormone (FSH) level of a high-cholesterol diet. Not only that but there are also limited proven supplements available for male infertility problems. Hence, this study aimed to determine the effects of TH on the sperm profile and follicularstimulating hormone (FSH) level of high cholesterol diet (HCD) administered to rats.